2015
DOI: 10.11646/zootaxa.3925.2.6
|View full text |Cite
|
Sign up to set email alerts
|

A new bathyal mysid of the family Petalophthalmidae (Crustacea: Mysida) <br />from the Bismarck Sea (Western Tropical Pacific Ocean)

Abstract: A new species of the genus Petalophthalmus (Crustacea: Mysida: Petalophthalmidae) is described, based on one specimen collected from the Bismarck Sea (Papua New Guinea, Western Pacific Ocean). This species can be distinguished from the other species of the genus Petalophthalmus by the globular cornea and the armature of the telson. This new species lives between 800 and 1065 m depth. A discussion on the geographic and bathymetric distribution and an identification key to world species of Petalophthalmus are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Reduction of the lacinia mobilis on one of the two mandibles is also found in at least nine bathyal to abyssal species of the genera Hansenomysis Stebbing, 1893, Bacescomysis Murano & Krygier, 1985, Petalophthalmus and Ipirophthalmus gen. nov. These three genera belong to the Petalophthalmidae and are morphologically remote from Abyssomysis gen. nov. and Mysimenzies Băcescu, 1971. In the respective species of Petalophthalmidae, the lacinia mobilis of the left or the right mandible is reduced to varying degrees (Birstein & Tchindonova 1958;Băcescu 1971aBăcescu , 1971bSan Vicente & Corbari 2015;present study). Based on the strong setation of perioral structures Băcescu (1971b) argued that Hansenomysis species are detritus feeders.…”
Section: Feeding and Deep-sea Adaptationmentioning
confidence: 86%
See 2 more Smart Citations
“…Reduction of the lacinia mobilis on one of the two mandibles is also found in at least nine bathyal to abyssal species of the genera Hansenomysis Stebbing, 1893, Bacescomysis Murano & Krygier, 1985, Petalophthalmus and Ipirophthalmus gen. nov. These three genera belong to the Petalophthalmidae and are morphologically remote from Abyssomysis gen. nov. and Mysimenzies Băcescu, 1971. In the respective species of Petalophthalmidae, the lacinia mobilis of the left or the right mandible is reduced to varying degrees (Birstein & Tchindonova 1958;Băcescu 1971aBăcescu , 1971bSan Vicente & Corbari 2015;present study). Based on the strong setation of perioral structures Băcescu (1971b) argued that Hansenomysis species are detritus feeders.…”
Section: Feeding and Deep-sea Adaptationmentioning
confidence: 86%
“…These legs were reported as being different in the remaining two species here also assigned to Ipirophthalmus gen. nov.: Pillai (1968) reported an elongate endopod 4 ending in a brush of setae upon redescription of P. oculatus (now I. oculatus) based on a single specimen. San Vicente & Corbari (2015), however, concluded that Pillai (1968) may have confounded endopod 5 with endopod 4, due to the habitus of this specimen illustrated by Pillai (1968: fig. 1) with thoracopods 3-4 broken.…”
Section: Morphology Of the Petalophthalminae And Establishment Of Ipirophthalmus Gen Novmentioning
confidence: 92%
See 1 more Smart Citation